The association between the lactate to albumin ratio and all-cause mortality in cardiac arrest patients: an analysis of the MIMIC-IV database - Lulu Liu; Qian Ma; Guangzan Yu; Xuhou Ji; Hua He (European Journal of Medical Research)
Abstract Introduction Cardiac arrest (CA) is a critical condition with high mortality, despite advances in post-resuscitation care. Severe ischemia-reperfusion injury, systemic inflammation, nutritional status, and organ dysfunction contribute to poor prognosis, highlighting the need for reliable prognostic markers for early risk stratification. Lactate and albumin are well known to be involved in these pathological processes, making them potential biomarkers for prognostic assessment. This study aims to investigate the association between the lactate to albumin ratio (LAR) and all-cause mortality in patients with CA. Methods Clinical data were collected from the MIMIC-IV (3.1) database. The individuals were categorized into four groups based on the quartiles of the LAR. The primary endpoint of the research was 30-day all-cause mortality, while the secondary endpoint was 90-day all-cause mortality. The association between the LAR and clinical outcomes was analyzed using Cox proportional hazards regression, restricted cubic splines, and Kaplan-Meier survival curves. Moreover, the predictive performance of the LAR for 30-day all-cause mortality in the CA population was evaluated using the Receiver Operating Characteristic (ROC) curve by calculating the Area Under the Curve (AUC). Results A total of 1311 patients with CA were enrolled in our study. After adjusting for confounders, each unit increase in the LAR was associated with a 20.1% and 19.6% increased risk of 30-day and 90-day all-cause mortality, respectively (P < 0.001), suggesting a possible nonlinear association. The Quartile 4 group exhibited a significantly higher mortality risk compared to the lowest quartile, when the LAR was treated as a categorical variable. Additionally, the ROC curve demonstrated moderate discriminatory ability of the LAR in recognizing 30-day all-cause mortality risk from the overall CA population (AUC: 0.69, 95% CI: 0.66–0.72), which was comparable to lactate but superior to albumin. Conclusion The LAR exhibits a strong and nonlinear association with both 30-day and 90-day all-cause mortality, with elevated levels significantly increasing mortality risk, even after adjusting for potential confounders and applying multiple statistical methods. The ROC curve showed moderate discriminative ability, highlighting the potential of the LAR as a prognostic indicator in patients with CA.